Web platform for the identification and analysis of events on twitter (2020)
Due to the great popularity of social networks among people, businesses, public figures, etc., there is a need for automatic methods to facilitate the search, retrieval, and analysis of large amounts of information. Given this situation, the Online Reputation Analyst (ORA) faces the challenge of identifying relevant issues around an event, product and/or public figure, from which it can propose different strategies to strengthen and/or reverse trends. Therefore, this paper proposes and describes a web tool whose main objective is to support the tasks performed by an ORA. The proposed visualization techniques make it possible to immediately identify the relevance and scope of the opinions generated about an event that took place on Twitter.